Diagnosing poverty, building communities [moving pictures] - International Action for Liberation; Ceukelaire, Wim De; Libres, Bedette P. ([Quezon city, Philippines] KODAO Production for INTAL, 2005)
This is how Manang Anita, a Philippine community health worker, summarizes the essence of her community's struggle for health. Diagnosing Poverty, building community tells the story of Filipinos who take their health and their future into their own hands like the poor peasants in Bukidnon, Mindanao, and Gene and Julie, two young doctors from Manila.
It is the story of Baby Jesie, a child from a remote indigenous community, who almost died because of his government's neglect and wrong priorities. Most of all, it is the story of ordinary people's courage to organize themselves and mobilize their communities to overcome poverty and build a healthy society.
Keywords: Indigenpous people -- Bukidnon, Philippines; Poverty -- Philippines